Integrasi Fitur Dalam Membangun Dashboard Website Monitoring Resource Server Untuk Pt. Neural Technologies Indonesia - Firnawan, Rifqi; Iqba, Muhammad; Tra Doni Ginting, Edi (eProceedings of Applied Science, 2024)
Server monitoring in information technology infrastructureinfrastructure is essential for companies toensure optimal service for users. Withthe increasing need for availability andservice availability and reliability, PT Neural Technologies Indonesiafaces challenges in maintaining the performance andsecurity of their servers. In this context, designingserver resource monitoring website becomes veryimportant. The proposed system aims toenable real-time monitoring and analysis of server performanceperformance in real-time through comprehensive integration.The system is designed to collect data fromvarious servers, analyze the information, andprovide reports to the administrator. ByThus, potential problems can be identified and addressed before they impact users.before they impact users. The result of this designThe results of this design are expected to improve the availability, performanceand security of the server infrastructure. This system is alsoexpected to optimize the management ofresources for PT Neural Technologies Indonesia, by providing an effective tool for monitoring andproviding an effective tool to monitor andmaintain server performance. Thus, the companycan ensure that the services provided tousers remain optimized and free from disruptions. Keywords: real-time, monitoring, server resources